Revisiting the Cause of the 1989–2009 Arctic Surface Warming Using the Surface Energy Budget: Downward Infrared Radiation Dominates the Surface Fluxes. Issue 20 (28th October 2017) - Lee, Sukyoung; Gong, Tingting; Feldstein, Steven B.; Screen, James A.; Simmonds, Ian
Abstract: The Arctic has been warming faster than elsewhere, especially during the cold season. According to the leading theory, ice‐albedo feedback warms the Arctic Ocean during the summer, and the heat gained by the ocean is released during the winter, causing the cold‐season warming. Screen and Simmonds (2010; SS10) concluded that the theory is correct by comparing trend patterns in surface air temperature (SAT), surface turbulence heat flux (HF), and net surface infrared radiation (IR). However, in this comparison, downward IR is more appropriate to use. By analyzing the same data used in SS10 using the surface energy budget, it is shown here that over most of the Arctic the skin temperature trend, which closely resembles the SAT trend, is largely accounted for by the downward IR, not the HF, trend. Key Points: Surface temperature should be compared with downward infrared radiation and not net infrared radiation The Arctic surface temperature trend is driven primarily by downward infrared radiation and not surface turbulent fluxes The downward infrared radiation trend is associated with the intraseasonal moisture intrusion trend Plain Language Summary: The Arctic has been warming faster than elsewhere, especially during the fall and winter. According to the leading theory, ice‐albedo feedback warms the Arctic Ocean during the summer, and the heat gained by the ocean is released during the fall and winter, causing warming in these seasons. Deviating from this theory, it is shown here that over most of the Arctic, the skin temperature trend, which closely resembles the SAT trend, is largely accounted for by the downward infrared radiation, not the ocean‐to‐atmosphere heat flux, trend.